2003
DOI: 10.1007/s10029-003-0125-1
|View full text |Cite
|
Sign up to set email alerts
|

Carboxymethylcellulose coated on visceral face of polypropylene mesh prevents adhesion without impairing wound healing in incisional hernia model in rats

Abstract: Adhesions between viscera and mesh may result in intestinal obstruction and fistulae formation. Fewer adhesions with sodium carboxymethylcellulose (SCMC)-coated polypropylene mesh (PM) has been reported, but impaired wound healing was the major concern. We investigated the adhesion-prevention effect of SCMC in different concentrations, as coating only on visceral face of PM and its effects on wound healing. A full-thickness abdominal wall defect was created in 28 rats, which were then divided into three groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…However, most of the published work has involved the use of resorbable coating materials, such as cellulose, collagen, and omega-3 fatty acids [30][31][32]. These have been shown to be effective in the short-term, but the protective effects are lost in the long-term as a result of coating breakdown through phagocytosis [33].…”
Section: Discussionmentioning
confidence: 98%
“…However, most of the published work has involved the use of resorbable coating materials, such as cellulose, collagen, and omega-3 fatty acids [30][31][32]. These have been shown to be effective in the short-term, but the protective effects are lost in the long-term as a result of coating breakdown through phagocytosis [33].…”
Section: Discussionmentioning
confidence: 98%
“…The use of both H-CMC PTFE mesh and PET mesh and were found to be equally effective in incisional hernia repair while decreasing intra-abdominal adhesions. It is also presented that wound healing may be affected with the use of prosthetic materials and anti-adhesive agents (15,16). In order to reduce intra-abdominal adhesions and increase the abdominal tissue support, various prosthetic materials were used.…”
Section: Discussionmentioning
confidence: 99%
“…In several animal studies the advantage of different absorbable barriers could be demonstrated, though no material so far seems to be able to prevent adhesion formation completely. [17][18][19][20] Furthermore the combination of two or more different materials and/or structures changes the textile and biological properties. Certainly, this results in an increase of foreign material and most often lead to a reduction of mesh elasticity.…”
Section: Discussionmentioning
confidence: 99%